The historic sanctuary of Chacamarca, as an ecotourism service in Junin - Acuña-Aguilar, Grimaldo R. (2024)
The objective of the study was to evaluate the functioning of the Chacamarca Historical Sanctuary as an ecotourism service in Junín, and to evaluate the degree of user satisfaction. This will allow us to examine the implications of ecotourism in Chacamarca for local communities, considering that the development of sustainable ecotourism can generate employment, diversify the local economy and promote community participation in the management of natural and cultural resources. The study was basic in nature, had a quantitative approach, non-experimental design and descriptive level. The population was made up of the inhabitants of the four districts: Carhuamayo, Ondores, Ulcumayo and Junín. The sample was 379 inhabitants of the aforementioned districts. To collect the data, a 14-item questionnaire was used. Tourist satisfaction in the Chacamarca Historical Sanctuary depends on the quality of services and infrastructure, and improving accessibility and basic services is essential. Ecotourism can have a significant impact on the population of Junín, generating employment and diversifying the local economy, while promoting sustainable development and the conservation of natural and cultural heritage.